2021
DOI: 10.1371/journal.pone.0245582
|View full text |Cite
|
Sign up to set email alerts
|

Method comparison studies of telomere length measurement using qPCR approaches: A critical appraisal of the literature

Abstract: Use of telomere length (TL) as a biomarker for various environmental exposures and diseases has increased in recent years. Various methods have been developed to measure telomere length. Polymerase chain reaction (PCR)-based methods remain wide-spread for population-based studies due to the high-throughput capability. While several studies have evaluated the repeatability and reproducibility of different TL measurement methods, the results have been variable. We conducted a literature review of TL measurement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 85 publications
0
35
0
Order By: Relevance
“…Because qPCR can be performed with high throughput platforms with relatively small amount of specimen at low cost, it remains the most widely used method for large-scale epidemiological and population studies. However, the high sensitivity of this assay format to the impacts of preanalytical and analytical factors cast some doubts on the accuracy and reproducibility of this method ( Boardman et al, 2014 ; Cunningham et al, 2013 ; Dagnall et al, 2017 ; Denham et al, 2014 ; Hofmann et al, 2014 ; Lin et al, 2018 ; Raschenberger et al, 2016 ; Lindrose et al, 2021 ). Sample sources, DNA extraction methods and storage conditions, PCR conditions, assay re-agents and data analysis methods have all been reported to influence the final data output.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Because qPCR can be performed with high throughput platforms with relatively small amount of specimen at low cost, it remains the most widely used method for large-scale epidemiological and population studies. However, the high sensitivity of this assay format to the impacts of preanalytical and analytical factors cast some doubts on the accuracy and reproducibility of this method ( Boardman et al, 2014 ; Cunningham et al, 2013 ; Dagnall et al, 2017 ; Denham et al, 2014 ; Hofmann et al, 2014 ; Lin et al, 2018 ; Raschenberger et al, 2016 ; Lindrose et al, 2021 ). Sample sources, DNA extraction methods and storage conditions, PCR conditions, assay re-agents and data analysis methods have all been reported to influence the final data output.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The ICC across individuals was 0.77, including treatment week as a fixed factor. Since true TL was presumably changing over the course of the study, 0.77 represents a minimum estimate of the technical repeatability of the TL measurements and suggests measurement precision was acceptably high [42]. All telomere measurements were conducted blind to treatment.…”
Section: Telomere Lengthmentioning
confidence: 99%
“…Most epidemiological studies utilizing TL measurements generated using qPCR either rely on instrument software to estimate amplification efficiency based on a standard-curve, or do not report how efficiency estimates are derived. According to one study, PCR efficiency is the least commonly reported metric in comparative studies utilizing TL measurements generated using qPCR (Lindrose et al, 2021). These norms of practice run counter to new guidelines issued by the Telomere Research Network for studies using qPCR (doi: 10.31219/osf.io/9pzst), as well as the MIQE guidelines for real-time qPCR experiments more broadly (Bustin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns expressed about accurate measurement of amplification efficiency for qPCR more broadly (Bustin et al, 2009), have yet to receive substantial attention in telomere research. In fact, details related to PCR efficiency are the least commonly reported metric in comparative studies utilizing TL measurements generated using qPCR (Lindrose et al, 2021). This oversight is concerning, given the increased susceptibility of TL measurements generated via qPCR to variability in amplification efficiency.…”
Section: Introductionmentioning
confidence: 99%